A game-theoretic implication of the Riemann Hypothesis - Christian Ewerhart (University of Zurich, Department of Economics, 2023)
The Riemann Hypothesis (RH) is one of the major unsolved problems in pure mathematics. In this note, a parameterized family of non-cooperative games is constructed with the property that, if RH holds true, then any game in this family admits a unique Nash equilibrium. We argue that this result is not degenerate. Indeed, neither is the conclusion a tautology, nor is RH used to define the family of games.
Keywords: 330; Riemann hypothesis; Nash equilibrium